Morphosyntactic variation in an emerging dialect of eastern North Carolina Spanish - Lawrence, Anna Alexia (East Carolina University, 2016)
For the past several decades, the Spanish-speaking population in eastern North Carolina (eNC) has been increasing rapidly. While much is known of other Spanish varieties spoken in major cities in the US, little is known about the formation of Spanish communities in the rural South. This project aims to fill that void by adding to our knowledge of Spanish morphosyntax by noting specific properties that make this emerging Spanish community’s expression of explicit subject in Spanish different than other bilingual Spanish varieties around the U.S. Methodology for the study included: (a) collection of speech samples through sociolinguistic interviews, and (b) participant profiles through a Background Language Proficiency (BLP) Questionnaire. Results from our study conducted on 1,309 tokens from 18 first- and second-generation speakers of Mexican Spanish indicated a statistically significant difference in subject expression based on time spent in the region of eNC, bilingual dominance in English, country of birth, and individual rates of expression. Additionally, preliminary results indicate an influence of verbal person as a predictor of subject expression. Overall, the findings from this study indicate an emerging effect of bilingual contact between English and Spanish in the region of eNC. This justifies the need to investigate whether the region plays a different role in constructing the linguistic identities of its Hispanic inhabitants separately from other historically bilingual U.S. cities.
Keywords: Subject expression, Spanish in the U.S., morphosyntactic variation